Assessing the accuracy of visual blood loss estimation in postpartum hemorrhage in Shanghai hospitals: A web‐based survey for nurses and midwives. Issue 23 (22nd May 2021) - Liu, Ying; Zhu, Wei; Shen, Ying; Qiu, Jingbo; Rao, Lin; Li, Hong
Abstract: Aims and objectives: This study aimed at evaluating the accuracy of visual estimated blood loss in postpartum haemorrhage by midwives and nurses, as well as exploring its influencing factors. Background: Timely recognition of postpartum haemorrhage is critical in saving maternal lives. Yet midwives and nurses can barely distinguish whether the blood loss has reached a life‐threatening amount without precise measurement. Understanding their ability to accurately estimate the amount of blood loss and the influencing factors can help improve this ability with effective measures. Design: This research was a multicenter cross‐sectional survey with convenient sampling. Material and Methods: Using a modified online visual estimation questionnaire of blood loss, the QR code of this survey was sent to midwives and obstetrical nurses engaged in clinical practice in secondary and tertiary hospitals in Shanghai. A descriptive analysis was performed with demographics and the responses of visual estimated blood loss of each volume. The difference and consistency of the responses of each volume were evaluated. The relationship between each demographic characteristic and accuracy was explored. STROBE statement checklist was chosen for reporting the study process. Results: A total of 361 midwives and nurses participated in the survey. The finding showed an overall accuracy of 30.52% (1763/5776), with 25.3% and 18.0% subjects distinguishing postpartum haemorrhage (500 ml) and severe postpartum haemorrhage (1000 ml), respectively. The Kappa coefficients were slight to moderate (0.037–0.590). There were no differences among the categories of gender, age, academic degree, position, title, working experience in years, working department and reported methods of blood loss estimation with regard to accuracy. However, having institutional guidance for blood loss calculation showed a significant relationship with higher accuracy. Relevance to clinical practice: While representing a relatively well‐developed area in China, the accuracy of visual estimated blood loss was not satisfactory, as suggested in other developed countries around the world. Training and institutional guidance on blood loss quantification should be provided in midwifery settings, regardless of how the level of medical development is advanced. Conclusions: The accuracy of VEBL was low even with a visual aid, especially when the volume exceeds 500 ml. To improve accuracy, institutions should make standardadized assessment guidance and provide regular training for blood loss quantification.